Positive electrode active material for lithium secondary battery and method for producing same
By employing a heat treatment and boron coating process on a nickel, cobalt, and manganese precursor, the method addresses thermal and structural instability in lithium nickel cobalt metal oxides, enhancing battery safety and stability.
Patent Information
- Application Number
- JP2024538211
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-23
- Filing Date
- 2022-12-22
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2042-12-22
AI Technical Summary
Lithium nickel cobalt metal oxides used in positive electrodes of lithium secondary batteries face issues with thermal stability and structural instability, particularly when nickel content is increased for higher capacity, leading to potential battery explosions and fires due to rapid oxygen desorption.
A manufacturing method involving primary and secondary heat treatments of a nickel, cobalt, and manganese precursor, followed by a boron coating, forms a lithium transition metal oxide with a cobalt coating at the particle interface, enhancing structural stability and thermal resistance.
The method results in a positive electrode active material with improved high-temperature life characteristics and reduced gas generation, ensuring safer and more stable battery performance.
Smart Images

Figure 2025500473000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0185900 filed on December 23, 2021, and all contents disclosed in the documents of said Korean patent application are incorporated as part of this specification.
[0002] The present invention relates to a positive electrode active material for a lithium secondary battery and a method for producing the positive electrode active material. [Background technology]
[0003] With the technological development and increasing demand for mobile devices, the demand for secondary batteries as an energy source is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.
[0004] Lithium transition metal composite oxides are used as the positive electrode active material of lithium secondary batteries, and among them, lithium cobalt composite metal oxides such as LiCoO2, which have high working voltage and excellent capacity characteristics, are mainly used. However, LiCoO2 has very poor thermal characteristics due to the instability of the crystal structure caused by delithiation. In addition, the LiCoO2 is expensive, so there is a limit to its mass use as a power source in fields such as electric vehicles.
[0005] As a material to be used in place of LiCoO2, lithium manganese composite metal oxides (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compounds (LiFePO4, etc.), lithium nickel composite metal oxides (LiNiO2, etc.), etc. have been developed. Among them, research and development of lithium nickel composite metal oxides, which have a high reversible capacity of about 200 mAh / g and can easily realize large-capacity batteries, has been actively carried out. However, LiNiO2 has inferior thermal stability compared to LiCoO2, and if an internal short circuit occurs due to external pressure in a charged state, the positive electrode active material itself decomposes, causing the battery to explode and catch fire. Therefore, lithium nickel cobalt metal oxides, in which part of Ni is replaced with Co, Mn, or Al, have been developed as a method to maintain the excellent reversible capacity of LiNiO2 and improve its low thermal stability.
[0006] However, the lithium nickel cobalt metal oxide has low structural stability and capacity. In particular, when the nickel content is increased to improve the capacity characteristics, the nickel becomes Ni as the charging and discharging process proceeds. 2+ From Ni 3+ Or Ni 4+ This causes rapid desorption of oxygen, further reducing the structural stability.
[0007] Therefore, there is a need for the development of a positive electrode active material that contains a lithium nickel cobalt metal oxide containing a high content of Ni that exhibits high capacity characteristics, has excellent structural stability of the lithium nickel cobalt metal oxide, and can be used to produce a high capacity and long life battery. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2010-92848 A Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention aims to produce a positive electrode active material that contains a lithium transition metal oxide with a high nickel content, and that has improved life characteristics at high temperatures and suppressed gas generation by coating the surfaces and crystal grains of lithium transition metal oxide particles by controlling the temperatures of a primary heat treatment and a secondary heat treatment. [Means for solving the problem]
[0010] In order to achieve the above object, the present invention provides a method for producing a positive electrode active material, the method including: (S1) preparing a positive electrode active material precursor, the positive electrode active material precursor containing nickel, cobalt, and manganese, and containing 60 mol % or more of nickel among all metals other than lithium; (S2) mixing the positive electrode active material precursor with a lithium raw material, and performing a primary heat treatment at 660 to 800°C to form a lithium transition metal oxide in the form of secondary particles in which primary particles are aggregated; (S3) mixing the lithium transition metal oxide with a cobalt ion-containing source, and performing a secondary heat treatment at 640 to 800°C to form a secondary heat-treated product; (S4) washing the secondary heat-treated product with water; and (S5) dry-mixing the washed secondary heat-treated product with a boron coating source, and performing a heat treatment.
[0011] The present invention also provides a positive electrode active material comprising a lithium transition metal oxide in the form of secondary particles comprising nickel, cobalt, and manganese and in which primary particles are aggregated, wherein a coating layer containing cobalt is formed on the surface of the secondary particles of the lithium transition metal oxide and at interfaces between the primary particles located inside the secondary particles, and the primary particles have a cobalt content of 7.0 mol % or more relative to the total metal content, and a spectrum of the lithium transition metal oxide measured by TEM-EELS, which is a combination of a transmission electron microscope (TEM) and electron energy loss spectroscopy (EELS), includes a first peak located in a region corresponding to a depth of 50 nm from the surface of the primary particles and located in a core portion of the secondary particles, the surface portion of the secondary particles being a region corresponding to a depth of 50 nm from the surface of the secondary particles, and the core portion of the secondary particles being a region corresponding to a depth of more than 3 μm from the surface of the secondary particles, and the first and second peaks being peaks in the range of 180 to 200 eV in the TEM-EELS spectrum. Effect of the Invention
[0012] According to the present invention, a coating effect is achieved by controlling the degree of cobalt doping of the surface and crystal grains of a lithium transition metal oxide particle containing a high nickel content, and finally, a boron and cobalt composite coating part is formed, thereby making it possible to manufacture a positive electrode active material with improved structural stability.
[0013] When a secondary battery is manufactured using the positive electrode active material manufactured according to the present invention, the high-temperature life characteristics can be improved and the amount of gas generation can be reduced. [Brief description of the drawings]
[0014] [Figure 1] 1(a) and (b) are SEM (Scanning electron microscopy) images of the surfaces of the positive electrode active materials produced in Examples 1 and 2, respectively. [Diagram 2]1(a) and 1(b) are SEM images of the surfaces of the positive electrode active materials produced in Comparative Examples 1 and 4, respectively. [Diagram 3] 1(a) and 1(b) are TEM data of the surface and the interior, respectively, of the positive electrode active material produced in Example 1. [Figure 4] 6(a) and 6(b) are TEM images of the surface and the interior, respectively, of the positive electrode active material produced in Example 2. FIG. [Diagram 5] FIG. 13 is a diagram showing TEM data of the surface of the positive electrode active material produced in Comparative Example 3. [Figure 6] 1 is a graph showing high-temperature life characteristics of secondary batteries manufactured using positive electrode active materials according to an example and a comparative example. [Figure 7] 4 is a graph showing the amount of gas generated during high-temperature storage of secondary batteries manufactured using positive electrode active materials according to examples and comparative examples. [Figure 8] FIG. 2A shows the TEM-EELS measurement positions and FIG. 2B shows the TEM-EELS spectrum for the surface portion of the secondary particle in Example 1. [Figure 9] FIG. 2A shows TEM-EELS measurement positions and FIG. 2B shows TEM-EELS spectra for the secondary particle core portion of Example 1. [Figure 10] FIG. 13A shows the TEM-EELS measurement positions and FIG. 13B shows the TEM-EELS spectrum for the surface portion of the secondary particle in Example 2. [Figure 11] FIG. 13A shows the TEM-EELS measurement positions and FIG. 13B shows the TEM-EELS spectrum for the secondary particle core portion of Example 2. [Figure 12] FIG. 13A shows the TEM-EELS measurement positions and FIG. 13B shows the TEM-EELS spectrum for the surface portion of a secondary particle in Comparative Example 5. [Figure 13] FIG. 13A shows the TEM-EELS measurement positions and FIG. 13B shows the TEM-EELS spectrum for the secondary particle core portion of Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will now be described in further detail in order to facilitate understanding of the present invention.
[0016] The terms and words used in the description of the present invention and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0017] Method for producing positive electrode active material The method for producing a positive electrode active material of the present invention includes the steps of: (S1) preparing a positive electrode active material precursor, which contains nickel, cobalt, and manganese, and contains 60 mol % or more of nickel among all metals other than lithium; (S2) mixing the positive electrode active material precursor with a lithium raw material and performing a primary heat treatment at 660 to 800°C to form a lithium transition metal oxide in the form of secondary particles in which primary particles are aggregated; (S3) mixing the lithium transition metal oxide with a cobalt ion-containing source and performing a secondary heat treatment at 640 to 800°C to form a secondary heat-treated product; (S4) washing the secondary heat-treated product with water; and (S5) dry-mixing the washed secondary heat-treated product with a boron coating source and performing a heat treatment.
[0018] Step (S1) A positive electrode active material precursor is prepared, which contains nickel, cobalt and manganese, with nickel being contained in an amount of 60 mol % or more of all metals other than lithium.
[0019] The positive electrode active material precursor may be a commercially available positive electrode active material precursor, or may be prepared by a method for preparing a positive electrode active material precursor known in the art.
[0020] For example, the precursor may be prepared by adding an ammonium cation-containing complex former and a basic compound to a transition metal solution containing a nickel-containing raw material, a cobalt-containing raw material, and a manganese-containing raw material, and then subjecting the mixture to a coprecipitation reaction.
[0021] The nickel-containing raw material may be, for example, a nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be, but is not limited to, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, a fatty acid nickel salt, a nickel halide, or a combination thereof.
[0022] The cobalt-containing source material may be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, or a combination thereof, but is not limited thereto.
[0023] The manganese-containing raw material may be, for example, manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxide, or a combination thereof, and specifically may be manganese oxides such as Mn2O3, MnO2, Mn3O4, etc.; manganese salts such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate, and manganese fatty acid salt; manganese oxyhydroxide, manganese chloride, or a combination thereof, but is not limited thereto.
[0024] The transition metal solution may be prepared by adding a nickel-containing raw material, a cobalt-containing raw material, and a manganese-containing raw material to a solvent, specifically, water or a mixed solvent of an organic solvent (e.g., alcohol, etc.) that can be uniformly mixed with water, or by mixing an aqueous solution of the nickel-containing raw material, an aqueous solution of the cobalt-containing raw material, and the manganese-containing raw material.
[0025] The ammonium cation-containing complexing agent may be, for example, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, NH4CO3, or a combination thereof, but is not limited thereto. Meanwhile, the ammonium cation-containing complexing agent may be used in the form of an aqueous solution, and the solvent may be water or a mixture of water and an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water.
[0026] The basic compound may be a hydroxide of an alkali metal or an alkaline earth metal, such as NaOH, KOH, or Ca(OH)2, a hydrate thereof, or a combination thereof. The basic compound may also be used in the form of an aqueous solution, and the solvent may be water or a mixture of water and an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water.
[0027] The basic compound is added to adjust the pH of the reaction solution, and may be added in an amount such that the pH of the metal solution becomes 11 to 13.
[0028] Meanwhile, the coprecipitation reaction may be carried out at a temperature of 40 to 70°C under an inert atmosphere such as nitrogen or argon. Through the above process, nickel-cobalt-manganese hydroxide particles are generated and precipitated in the reaction solution. By adjusting the concentrations of the nickel-containing raw material, the cobalt-containing raw material, and the manganese-containing raw material, a precursor having a nickel content of 60 mol% or more of the total metal content can be produced. The precipitated nickel-cobalt-manganese hydroxide particles are separated and dried by a conventional method to obtain a nickel-cobalt-manganese precursor. The precursor may be secondary particles formed by agglomeration of primary particles.
[0029] Step (S2) The positive electrode active material precursor and a lithium raw material are mixed and subjected to a primary heat treatment at 660 to 800° C. to form a lithium transition metal oxide in the form of secondary particles in which primary particles are aggregated.
[0030] In the present invention, the term "primary particle" refers to the smallest particle unit that can be distinguished as a single mass when a cross section of a positive electrode active material is observed with a scanning electron microscope (SEM), and may consist of one crystal grain or multiple crystal grains.
[0031] In the present invention, the term "secondary particle" refers to a secondary structure formed by the aggregation of a plurality of primary particles.
[0032] The lithium source material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or oxyhydroxide, and is not particularly limited as long as it is soluble in water. Specifically, the lithium source material may be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, or Li3C6H5O7, and any one or a mixture of two or more of these may be used.
[0033] The lithium transition metal oxide is a high-concentration nickel (Ni-rich) lithium transition metal oxide containing 60 mol % or more of nickel among all metals other than lithium, more preferably 70 mol % or more, or 80 mol % or more, and even more preferably 85 mol % or more of nickel (Ni). By satisfying the nickel (Ni) content of 60 mol % or more among all metals other than lithium in the lithium transition metal oxide, it is possible to ensure high capacity.
[0034] More specifically, the lithium transition metal oxide may be represented by the following Formula 1.
[0035] [Chemical formula 1] Li a Ni 1-(b+c+c) Co b Mn c Q d O2
[0036] In the above formula, Q is one or more selected from the group consisting of Al, Si, V, Nb, Mo, Ta, Y, La, Sn, Zr, B, W, Mg, Ce, Hf, Ta, Ti, Sr, Ba, F, P, S, and La;
[0037] 0.9≦a≦1.1, 0≦b≦0.2, 0≦c≦0.2, 0≦d≦0.1, 0 <b+c+d≦0.4である。
[0038] In the lithium transition metal oxide of Formula 1, Li may be included in a content corresponding to a, i.e., 0.9≦a≦1.1. If a is less than 0.9, the capacity may decrease, and if it exceeds 1.1, the particles may be sintered during the firing process, making it difficult to manufacture the positive electrode active material. Considering the remarkable effect of improving the capacity characteristics of the positive electrode active material by controlling the Li content and the balance between sinterability during the manufacture of the active material, the Li may more preferably be included in a content of 1.0≦a≦1.05.
[0039] In the lithium transition metal oxide of Chemical Formula 1, Ni can be contained in an amount corresponding to 1-(b + c + d), for example, 0.6 ≦ 1-(b + c + d) < 1. When the content of Ni in the lithium transition metal oxide of Chemical Formula 1 is 0.6 or more, a sufficient amount of Ni is ensured to contribute to charge and discharge, and high capacity can be achieved. More preferably, Ni can be contained in an amount of 0.80 ≦ 1-(b + c + d) ≦ 0.99.
[0040] In the lithium transition metal oxide of Chemical Formula 1, Co can be contained in an amount corresponding to b, that is, 0 ≦ b ≦ 0.2. When the content of Co in the lithium transition metal oxide of Chemical Formula 1 exceeds 0.2, there is a risk of cost increase. Considering the remarkable improvement effect of capacity characteristics by including Co, more specifically, Co can be contained in an amount of 0.05 ≦ b ≦ 0.2.
[0041] In the lithium transition metal oxide of Chemical Formula 1, Mn can be contained in an amount corresponding to c, that is, in an amount of 0 < c ≦ 0.2. When c in the lithium transition metal oxide of Chemical Formula 1 exceeds 0.2, rather, the output characteristics and capacity characteristics of the battery may decrease. More specifically, Mn can be contained in an amount of 0.05 ≦ c ≦ 0.2.
[0042] In the lithium transition metal oxide of Chemical Formula 1, Q is one or more selected from the group consisting of Al, Si, V, Nb, Mo, Ta, Y, La, Sn, Zr, B, W, Mg, Ce, Hf, Ta, Ti, Sr, Ba, F, P, S, and La. Such metal elements can improve the stability of the active material and, as a result, improve the stability of the battery. Considering the improvement effect on life characteristics, Q can be contained in an amount corresponding to d, that is, in an amount of 0 ≦ d ≦ 0.2. When Q in the lithium transition metal oxide of Chemical Formula 1 exceeds 0.2, rather, the output characteristics and capacity characteristics of the battery may decrease. More specifically, Q can be contained in an amount of 0.05 ≦ d ≦ 0.2.
[0043] Furthermore, the positive electrode active material precursor and the lithium source material can be mixed so that the molar ratio of Li to metal (Li / metal ratio) is 1 to 1.3, preferably 1.05 to 1.1, and more preferably 1.04 to 1.09. When the nickel-containing transition metal hydroxide precursor and the lithium source material are mixed in the above range, a positive electrode active material exhibiting excellent capacity characteristics can be produced.
[0044] The primary heat treatment is carried out at a temperature of 660 to 800°C, more preferably 660°C or higher, or 680°C or higher, and 800°C or lower, or 790°C or lower, for example, 660 to 790°C.
[0045] By carrying out the primary heat treatment within the above range, there are advantages in that it is possible to ensure regular atomic arrangement and capacity due to the nickel composition of the lithium transition metal oxide, and to appropriately control grain size.
[0046] The primary heat treatment can be performed in an oxidizing atmosphere. When the primary heat treatment is performed in an oxidizing atmosphere, it is possible to obtain a sufficient amount of residual lithium impurities to form a coating material, and it is possible to obtain a positive electrode nickel-containing lithium transition metal oxide with excellent crystal grain development. For example, when the primary heat treatment is performed in an inert atmosphere such as a nitrogen atmosphere, the amount of residual lithium impurities is so large that metal oxide is not synthesized, and it may be difficult to form a coating material.
[0047] The primary heat treatment may be performed in an oxidizing atmosphere at a temperature of 660 to 800° C. for 4 to 10 hours or 4 to 7 hours.
[0048] Step (S3) The lithium transition metal oxide and a cobalt ion-containing source are mixed and subjected to a second heat treatment at 640 to 800° C. to form a second heat-treated product.
[0049] In the step (S3), a coating layer containing cobalt can be formed at the interface between the primary particles constituting the secondary particles of the lithium transition metal oxide by the secondary heat treatment.
[0050] In the manufacturing method of the present invention, as described above, a coating layer containing cobalt is formed on the surface of the secondary particles and on the interface between the primary particles located inside the secondary particles, thereby strengthening the surface before performing a water washing process, and finally forming a composite coating layer containing cobalt as described below. This coating portion can ultimately improve the problem of deterioration in the structural and chemical stability of the positive electrode active material, and can be used in secondary batteries that exhibit excellent high-temperature life characteristics.
[0051] In the present invention, the cobalt ion-containing source may include one or more selected from the group consisting of Co(OH)2, Co2O3, CoCO3, Co5(CO3)2(OH)6, Co3(PO4)2, CoF3, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)·6H2O, Co3O4, Co(SO4)2·7H2O and CoC2O4, and more preferably may be Co(OH)2 or Co3O4.
[0052] The cobalt ion-containing source may be 0.4 to 4 parts by weight, or 0.8 to 3 parts by weight, based on 100 parts by weight of the lithium transition metal oxide. By mixing the cobalt ion-containing source in the above range, a solid solution formed with an appropriate coating thickness can exhibit the advantages of improved capacity, high temperature life / resistance increase at the same level as that exhibited by the equivalent composition.
[0053] The secondary heat treatment is carried out at a temperature of 640 to 800°C, more preferably 640°C or higher, 660°C or higher, or 670°C or higher, and 800°C or lower, 780°C or lower, or 750°C or lower, for example, 660 to 780°C.
[0054] By carrying out the secondary heat treatment within the above range, a coating layer containing cobalt is formed not only on the surfaces of the secondary particles of the lithium transition metal oxide but also on the interfaces between the primary particles located inside, thereby providing the advantage of solid diffusion throughout the surfaces and cores of the secondary particles.
[0055] The secondary heat treatment may be performed at 640 to 800° C. for 4 to 10 hours, or 4 to 8 hours.
[0056] Step (S4) The step of washing the secondary heat-treated product with water can remove lithium by-products present on the surfaces of the lithium transition metal oxide particles.
[0057] In the case of high-concentration nickel (High-Ni) lithium transition metal oxide, since it is structurally unstable compared to lithium transition metal oxides with a low nickel content, more lithium by-products such as unreacted lithium hydroxide (LiOH) and lithium carbonate (Li2CO3) are generated during the manufacturing process. For example, in the case of a lithium composite metal oxide with a nickel fraction of less than 80 mol%, the amount of lithium by-products after synthesis is about 0.5 to 0.6 wt%, whereas in the case of a lithium composite metal oxide with a nickel fraction of 80 mol% or more, the amount of lithium by-products after synthesis is high at about 1 wt%. On the other hand, when a large amount of lithium by-products is present in the positive electrode active material, the lithium by-products react with the electrolyte to generate gas, causing a swelling phenomenon, which significantly reduces high-temperature stability. Therefore, a water washing process is required to remove the lithium by-products from the lithium transition metal oxide containing high concentration nickel.
[0058] The water washing step may be performed by adding the lithium transition metal oxide to a washing liquid such as distilled water or tap water, and stirring the mixture.
[0059] The temperature of the washing solution used in the washing may be 1 to 80° C., or 5 to 80° C. The washing time may be 3 to 60 minutes, more preferably 5 to 40 minutes. When the washing temperature and washing time are within the above ranges, lithium by-products can be effectively removed.
[0060] The water washing step can be performed by mixing the washing solution and the lithium transition metal oxide in a ratio of 100:20 to 100:300 parts by weight, more preferably 100:50 to 100:200 parts by weight, and further preferably 100:60 to 100:180 parts by weight. When the mixing ratio of the washing solution and the lithium transition metal oxide satisfies the above range, lithium by-products can be effectively removed and surface defects of the lithium transition metal oxide can be reduced as much as possible.
[0061] Step (S5) The water-washed secondary heat-treated product and a boron coating source are dry-mixed and then heat-treated.
[0062] The heat treatment can form a boron coating on the surface of the lithium transition metal oxide particles. In the present invention, the stability and gas generation phenomenon are improved by coating the surface of the lithium transition metal oxide particles.
[0063] The boron coating source is H3BO3, B4C, B2O3, BF3, (C3H7O)3B, (C6H5O)3B, [CH3(CH2)3O]3B, C 13 H 19 The boron coating source may include at least one selected from the group consisting of O3, C6H5B(OH)2 and B2F4, and more preferably H3BO3. H3BO3 has a relatively low melting point and can coat not only the surface but also the inside of the secondary particle core, which is useful for improving the long life. The boron coating source may be mixed in an amount of 0.01 to 0.90 parts by weight, and more preferably 0.30 to 0.60 parts by weight, based on 100 parts by weight of the lithium transition metal oxide.
[0064] Within this range, a cobalt-containing boron coating layer may be formed with an appropriate thickness on the surfaces of the secondary particles of the lithium transition metal oxide and on the interfaces between the primary particles located inside the secondary particles.
[0065] The water-washed secondary heat-treated product and a boron coating source are dry-mixed, and then heat-treated at 200 to 750° C. to form the composite coating portion. The heat treatment can be more preferably performed at 200 to 500° C.
[0066] Within this range, no unreacted cobalt by-products are formed, and no lithium by-products are produced due to boron, and a composite coating layer can be smoothly formed.
[0067] In addition, a drying step may be performed before the water-washed secondary heat-treated product is dry-mixed with the boron coating source. For example, the secondary heat-treated product may be washed with water, dried at 80 to 140°C, and then dry-mixed with the boron coating source and heat-treated.
[0068] positive electrode active material The positive electrode active material of the present invention includes a lithium transition metal oxide in the form of secondary particles in which primary particles are aggregated, the lithium transition metal oxide includes a coating layer containing cobalt formed on the surface of the secondary particles of the lithium transition metal oxide and at interfaces between the primary particles located inside the secondary particles, the primary particles have a cobalt content of 7.0 mol % or more relative to the total metal, the lithium transition metal oxide includes a spectrum measured by TEM-EELS, which is a combination of a transmission electron microscope (TEM) and electron energy loss spectroscopy (EELS), which includes a first peak located in a region corresponding to a depth of 50 nm from the surface of the primary particles located in a surface portion of the secondary particles, and a second peak located in a region corresponding to a depth of 50 nm from the surface of the primary particles located in a core portion of the secondary particles, the surface portion of the secondary particles being a region corresponding to a depth of 50 nm from the surface of the secondary particles, and the core portion of the secondary particles being a region corresponding to a depth of more than 3 μm from the surface of the secondary particles, and the first and second peaks being peaks in the range of 180 to 200 eV in the TEM-EELS spectrum.
[0069] The intensity ratio of the first peak to the second peak may be 1:0.5 to 1:20, and specifically, 1:0.7 to 1:15, or 1:1 to 1:10.
[0070] The first peak is 1*10 3 ~30*10 3 The strength of the 3 ~30*10 3 , 2*10 3 ~28*10 3 , or 5*10 3 ~16*10 3 The strength of the can be shown.
[0071] The second peak is 20*10 3 ~60*10 3 , or 30*10 3 ~50*10 3 The strength of the can be shown.
[0072] Specifically, the TEM-EELS measurement can be performed by a method including the steps of preparing a TEM specimen using a Focused Ion Beam (FIB), defining an analysis area on the specimen, and obtaining an EELS spectrum in the analysis area. The EELS measurement conditions can be an acceleration voltage of 200 kV and a dispersion of 0.05 eV / channel.
[0073] The peaks appearing in the range of 180 to 200 eV in the TEM-EELS spectrum, ie, the first and second peaks, indicate the presence of boron contained in the surfaces of the primary particles forming the lithium transition metal oxide.
[0074] That is, when the lithium transition metal oxide contained in the positive electrode active material of the present invention is subjected to TEM-EELS measurement of the primary particles located at the surface and core of the secondary particles, a boron peak is exhibited in a region corresponding to a depth of 50 nm from the surface, and the primary particles located at the surface of the secondary particles show a higher boron content than the primary particles located at the core.
[0075] By including boron as described above, the BET surface area that is increased by washing with water can be effectively reduced, ensuring the stability of the positive electrode active material, and realizing a reduced rate of increase in resistance and excellent life characteristics.
[0076] In addition, the primary particles may have a cobalt content relative to the total metal content of 10.0 mol % or more, 12.0 mol % or more, or 15.0 mol % or more.
[0077] As described above, the primary particles are aggregated on the surface and inside of the lithium transition metal oxide of the present invention, and a coating layer containing cobalt is formed on the interface between the primary particles, which results in a higher cobalt content both on the surface and inside of the secondary particles compared to a lithium transition metal oxide in which a coating layer containing cobalt is not formed on the interface between the primary particles.
[0078] In this way, a coating layer is formed on the interface between the primary particles, which results in excellent stability of the secondary particles, improved life characteristics at high temperatures, and suppression of problems such as gas generation.
[0079] The "surface portion" of the secondary particle may refer to a region from the surface of the secondary particle to a depth of 50 nm, i.e., a region from the outermost surface of the secondary particle to a depth of 0 to 50 nm. More specifically, it may refer to a region from the surface of the secondary particle to a depth of 10 nm, or a region from the surface of the secondary particle to a depth of 7 nm.
[0080] The "core" of the secondary particle may refer to a region corresponding to a depth of more than 3 μm from the surface of the secondary particle.
[0081] The positive electrode active material can be produced by the production method of the present invention described above, and can be represented by [Chemical Formula 1] as described above.
[0082] As described above, the lithium transition metal oxide of the present invention may have a concentration gradient in which cobalt gradually decreases from the surface layer to the center of the primary particle constituting the lithium transition metal oxide.
[0083] In the present invention, "exhibiting a concentration gradient in which the transition metal concentration gradually changes (increases or decreases)" means that the transition metal concentration exists in a concentration distribution that gradually changes throughout the particle. Specifically, the concentration distribution may have a difference of 0.1 to 5 mol %, more specifically 0.1 to 3 mol %, and even more specifically 1 to 2 mol %, in terms of the total number of moles of the transition metal contained in the positive electrode active material, per 1 μm in the particle.
[0084] The positive electrode active material according to the present invention may further include a coating layer on the surface of the lithium transition metal oxide.
[0085] The coating layer is formed on the surface of secondary particles of lithium transition metal oxide and may contain one or more coating elements (M) selected from the group consisting of B, Li, Al, F, W, Mo, Ti, Mn, Ca, Sr, Zr, Zn, Mg, Ca, Si, Sn and Nb.
[0086] The coating element may be included in an amount of 50 to 5,000 ppm, preferably 50 to 2,000 ppm, based on the total weight of the positive electrode active material. If the content of the coating element is too high, the coating layer may be formed too thick, which may adversely affect the capacity characteristics and resistance characteristics, and if the content of the coating element is too low, the electrolyte blocking effect is not sufficient.
[0087] As described above, when the surface of the lithium transition metal oxide includes a coating layer containing one or more coating elements selected from the group consisting of B, Li, Al, F, W, Mo, Ti, Mn, Ca, Sr, Zr, Zn, Mg, Ca, Si, Sn and Nb, the coating layer suppresses contact between the electrolyte and the lithium transition metal oxide, thereby obtaining the effect of suppressing the elution of the transition metal and the generation of gas, etc.
[0088] positive electrode The present invention also provides a positive electrode for a lithium secondary battery, which contains the positive electrode active material produced by the above-mentioned method.
[0089] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector and including the above-mentioned positive electrode active material.
[0090] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0091] The positive electrode active material layer may contain a conductive material and a binder in addition to the positive electrode active material.
[0092] In this case, the positive electrode active material may be contained in a content of 80 to 99 wt%, more specifically, 85 to 98 wt%, based on the total weight of the positive electrode active material layer. When contained in the above content range, excellent capacity characteristics can be exhibited.
[0093] In this case, the conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery to be constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in combination. The conductive material can be contained in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.
[0094] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.
[0095] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by applying a positive electrode mixture prepared by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent onto a positive electrode current collector, followed by drying and rolling. In this case, the types and contents of the positive electrode active material, binder, and conductive material are as described above.
[0096] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and may be used alone or in combination of two or more of these. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity during subsequent coating for the manufacture of a positive electrode, taking into consideration the coating thickness of the slurry and the manufacturing yield.
[0097] Alternatively, the positive electrode can be produced by casting the positive electrode mixture on a separate support, peeling it off from the support, and laminating the resulting film on a positive electrode current collector.
[0098] Lithium secondary battery In addition, the present invention can provide an electrochemical device including the positive electrode. The electrochemical device can be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.
[0099] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode is as described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail below.
[0100] Also, the lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0101] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0102] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of usually 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0103] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.
[0104] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, the carbon material may be either low-crystalline carbon or high-crystalline carbon. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.
[0105] The negative electrode active material may be included in an amount of 80% by weight to 99% by weight based on the total weight of the negative electrode active material layer.
[0106] The binder is a component that facilitates bonding between the conductive material, the active material, and the current collector, and is usually added in an amount of 0.1 to 10 parts by weight per 100 parts by weight of the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.
[0107] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, specifically 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0108] For example, the negative electrode active material layer can be produced by applying a negative electrode mixture, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, onto a negative electrode current collector and drying the applied material; alternatively, the negative electrode mixture can be cast onto another support, and then peeled off from the support to obtain a film, which can be laminated onto the negative electrode current collector.
[0109] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent humidification ability of the electrolyte solution is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, etc., can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or a multilayer structure.
[0110] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0111] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0112] The organic solvent can be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Carbonate-based solvents such as ethylene carbonate (PC); alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes may be used. Among them, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, so that the electrolyte can exhibit excellent performance.
[0113] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably within the range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.
[0114] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of the total weight of the electrolyte.
[0115] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0116] Therefore, according to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.
[0117] The battery module or battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0118] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0119] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery in a medium- to large-sized battery module including a large number of battery cells. EXAMPLES
[0120] Working Example The present invention will be described in more detail with reference to the following examples. However, the following examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not limited thereto.
[0121] Example 1 Ni 0.96 Co 0.02 Mn 0.02 (OH)2, LiOH·H2O, ZrO2, and Al(OH)3 were mixed so that the Li / Metal (Ni, Co, Mn) molar ratio was 1.05:1, and the primary heat treatment was performed at 710℃ for 5 hours to obtain LiNi 0.94 Co 0.03 Mn 0.02 Al 0.02Lithium transition metal oxides of O2 were prepared.
[0122] After that, Co(OH)2 was mixed so that the molar ratio of Ni:Co:Mn:Al was 92:4:2:2, and then the secondary heat treatment was performed at 720℃ for 5 hours to obtain LiNi with a cobalt coating layer formed on the surface of the particles. 0.92 Co 0.04 Mn 0.02 Al 0.02 Lithium transition metal oxides with O2 composition were produced.
[0123] Then, the lithium transition metal oxide on which the cobalt coating layer was formed and water were mixed in amounts of 200 g and 240 g (weight ratio 1:1.2), respectively, and washed with water by stirring for 5 minutes. Then, the washed lithium transition metal oxide was treated with a filter press so that the moisture content was 3 to 15%, and then dried at 130°C.
[0124] Next, the dried lithium transition metal oxide and H3BO3 were mixed so that the weight ratio of H3BO3 was 100:0.57, and the mixture was heat-treated at 300° C. for 4 hours to prepare a positive electrode active material.
[0125] Example 2 A positive electrode active material was produced in the same manner as in Example 1, except that the temperature of the primary heat treatment was changed to 720°C and the temperature of the secondary heat treatment was changed to 680°C.
[0126] Comparative Example 1 A positive electrode active material was produced in the same manner as in Example 1, except that the temperature of the primary heat treatment was changed to 740°C and the temperature of the secondary heat treatment was changed to 600°C.
[0127] Comparative Example 2 A positive electrode active material was produced in the same manner as in Example 1, except that the temperature of the primary heat treatment was changed to 640°C and the temperature of the secondary heat treatment was changed to 720°C.
[0128] Comparative Example 3 LiNi was prepared in the same manner as in Example 1, except that Co(OH)2 was not mixed. 0.92 Co 0.04 Mn 0.02 Al0.02 Lithium transition metal oxides with O2 composition were produced.
[0129] Comparative Example 4 Ni 0.96 Co 0.02 Mn 0.02 (OH)2, LiOH·H2O, ZrO2, and Al(OH)3 were mixed so that the Li / Metal (Ni, Co, Mn) molar ratio was 1.05:1, and the primary heat treatment was performed at 720℃ for 5 hours to obtain LiNi 0.94 Co 0.02 Mn 0.02 Al 0.02 Lithium transition metal oxides of O2 were prepared.
[0130] After that, the weight ratio of lithium transition metal oxide and H3BO3 was adjusted to 100:0.57, and Co(OH)2 was mixed so that the molar ratio of Ni:Co:Mn:Al was 92:4:2:2, and then the secondary heat treatment was performed at 690°C for 5 hours to obtain LiNi 0.92 Co 0.04 Mn 0.02 Al 0.02 Lithium transition metal oxides with O2 composition were produced.
[0131] Comparative Example 5 Ni 0.96 Co 0.02 Mn 0.02 (OH)2, LiOH·H2O, ZrO2, and Al(OH)3 were mixed so that the Li / Metal (Ni, Co, Mn) molar ratio was 1.05:1, and the mixture was subjected to a primary heat treatment at 720℃ for 5 hours to obtain LiNi 0.94 Co 0.02 Mn 0.02 Al 0.02 Lithium transition metal oxides of O2 were prepared.
[0132] Thereafter, lithium acetate was mixed with 100 mL of ethanol (ethanol:lithium acetate weight ratio 100:1), and cobalt acetate was mixed so that the molar ratio of Ni:Co:Mn:Al was 92:4:2:2 to produce a transition metal-containing solution.
[0133] Then, the sol-gel reaction was carried out at 70°C, followed by vacuum drying at 150°C and secondary heat treatment at 690°C for 5 hours to obtain LiNi with a cobalt coating layer formed on the surfaces of the secondary and primary particles. 0.92 Co 0.04 Mn 0.02 Al 0.02 Lithium transition metal oxides with O2 composition were produced.
[0134] Experimental Example 1 The surfaces of the secondary particles of the positive electrode active material produced in Examples 1 and 2 and Comparative Examples 1 and 4 were observed using a scanning electron microscope.
[0135] 1(a) and 1(b) are SEM images of the surfaces of the positive electrode active materials prepared in Examples 1 and 2, respectively, and FIG. 2 is an SEM image of the surfaces of the positive electrode active materials prepared in Comparative Examples 1 and 4.
[0136] As shown in (a) and (b) of FIG. 1, in the case of the positive electrode active materials according to Examples 1 and 2, no residual Co source was observed, and it was confirmed that the inside of the secondary particles was coated through the interface of the primary particles. On the other hand, in the case of FIG. 2, unreacted Co and B solid solution were observed, and it was found that the thickness of the surface of the secondary particles was thick, which caused a decrease in capacity. This is believed to be because a coating layer was formed using a cobalt ion-containing source and a boron coating source simultaneously, or because the reaction of Co was hindered.
[0137] Experimental Example 2 The metal element distribution and content of the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 to 4 were analyzed using a TEM (instrument name: Titan G2 80-200 ChemiSTEM w / Gatan Continuum S EELS system, FEI Corporation). Prior to the analysis, a TEM sample with a thickness of 70 nm or less was prepared using an FIB (instrument name: Helios G4 UX, FEI Corporation) capable of target sampling of positive electrode material particles.
[0138] Specifically, the content (mol %) of each metal was calculated for the surface of the secondary particles of the lithium transition metal oxide, specifically, for the primary particles located at a depth of 20 nm from the outermost surface layer, and the results are shown in Table 1 below.
[0139] [Table 1]
[0140] Furthermore, the content (mol %) of each metal was calculated for the interior of the secondary particles of the lithium transition metal oxide, specifically, for the primary particles located at a depth of 5 to 6 μm from the outermost surface layer, and the results are shown in Table 2 below.
[0141] [Table 2]
[0142] The TEM data of Examples 1 and 2 and Comparative Example 3 are also shown in FIGS.
[0143] As shown in Tables 1 and 2, the positive electrode active materials of the Examples prepared according to the present invention had a higher cobalt content in both the primary particles located on the surface of the secondary particles and the primary particles located inside the secondary particles than the Comparative Examples. This confirmed that a coating layer containing cobalt was formed at the interface between the primary particles in the general area of the surface and inside of the secondary particles.
[0144] Experimental Example 3 Lithium secondary batteries were manufactured using the positive electrode active materials prepared in the Examples and Comparative Examples, and the resistance characteristics of each battery were evaluated.
[0145] Specifically, the positive electrode active materials prepared in the Examples and Comparative Examples, the carbon black conductive material, and the polyvinylidene fluoride binder were mixed in a weight ratio of 97.5:1.0:1.5 in N-methylpyrrolidone solvent to prepare a positive electrode slurry. The positive electrode slurry was applied to one side of an aluminum current collector, dried at 130° C., and rolled to prepare a positive electrode.
[0146] Next, the negative electrode active material (natural graphite), conductive material (carbon black) and binder (SBR+CMC) were mixed in water in a weight ratio of 95:1.5:3.5 to prepare a composition for forming a negative electrode. The composition for forming a negative electrode was applied onto a copper current collector, dried and then rolled to prepare a negative electrode.
[0147] A porous polyethylene separator was interposed between the positive and negative electrodes to prepare an electrode assembly, which was then placed inside a battery case, and an electrolyte was injected into the case to prepare a lithium secondary battery. The electrolyte was prepared by dissolving 1M LiPF6 in an organic solvent in which ethylene carbonate (EC): dimethyl carbonate (DMC): ethyl methyl carbonate (EMC) was mixed in a ratio of 3:4:3, and the electrolyte was injected to prepare the lithium secondary batteries according to Examples 1 and 2 and Comparative Examples 1 to 4.
[0148] A coin half cell was prepared using the cathode prepared as above and lithium metal as the anode. Each was charged to 4.25 V at a constant current / voltage of 0.1 C / 0.05 C at 25° C., and then discharged to 2.5 V at a constant current of 0.1 C to measure the initial charge capacity and the initial discharge capacity.
[0149] [Table 3]
[0150] The prepared lithium secondary batteries (3 cm×4 cm full cell) were charged at 25° C. at a constant current of 0.33 C to 4.25 V, and then initially charged and discharged at a constant current of 0.33 C to 2.5 V. Each secondary battery was charged at 45° C. at a constant current / constant voltage of 0.33 C / 0.05 C to 4.25 V, and then discharged at a constant current of 0.33 C to 2.5 V, which constitutes one cycle. 100 charge / discharge cycles were performed.
[0151] The capacity retention rate was expressed as a percentage of the capacity maintained at the 100th cycle relative to the capacity at the first cycle, and the resistance increase rate was expressed as a percentage of the increase in resistance at the 30th cycle relative to the resistance at the first cycle. The results are shown in Figure 6.
[0152] [Table 4]
[0153] As described above, it has been confirmed that when the cathode active material prepared according to the present invention is used in a secondary battery, a capacity can be realized without a decrease in initial capacity, and a secondary battery having excellent capacity retention, a low resistance increase rate, and improved life characteristics can be manufactured.
[0154] Experimental Example 4 The secondary battery manufactured in Experimental Example 1 was stored at 60° C. for up to 6 weeks and the amount of gas generated was observed. The volume increase rate (%) relative to the initial volume was calculated and the amount of gas generated was compared. The results are shown in FIG.
[0155] [Table 5]
[0156] As a result, it was confirmed that when the positive electrode active material of the Example was used, gas generation was significantly reduced and the degree of increase in volume was also reduced.
[0157] Experimental Example 5 8 to 13 show the results of analyzing the distribution and content of boron element in the positive electrode active material using a TEM (instrument name: Titan G2 80-200 ChemiSTEM w / Gatan Continuum EELS system, FEI Corporation).
[0158] Specifically, prior to the analysis, a TEM sample with a thickness of 70 nm or less was prepared using FIB (instrument name: Helios G4 UX, FEI) equipment capable of target sampling of positive electrode active material particles, and the measurement conditions were an acceleration voltage of 200 kV and a dispersion of 0.05 eV / channel.
[0159] In addition, the first and second peaks were measured by the TEM-EELS spectrum, and the values were summarized.
[0160] [Table 6]
[0161] As shown in Table 6, it was confirmed that the positive electrode active materials of Examples 1 and 2 according to the present invention exhibited the first and second peaks, which indicated the presence of boron.
Claims
1. (S1) preparing a positive electrode active material precursor containing nickel, cobalt, and manganese, and containing 60 mol % or more of nickel among all metals other than lithium; (S2) mixing the positive electrode active material precursor and a lithium source material, and performing a primary heat treatment at 660 to 800° C. to form a lithium transition metal oxide in the form of secondary particles in which primary particles are aggregated; (S3) mixing the lithium transition metal oxide with a cobalt ion-containing source and subjecting the mixture to a secondary heat treatment at 640 to 800° C. to form a secondary heat-treated product; (S4) washing the secondary heat-treated product with water; (S5) dry-mixing the washed secondary heat-treated product with a boron coating source and heat-treating the mixture.
2. 2. The method of claim 1, wherein the step (S3) comprises forming a coating layer containing cobalt at an interface between primary particles constituting secondary particles of the lithium transition metal oxide.
3. The method for producing a positive electrode active material according to claim 1 , wherein the lithium transition metal oxide is a compound represented by the following Chemical Formula 1: [Chemical formula 1] Li a Ni 1-(b+c+c) Co b Mn c Q d O 2 In the above formula, Q is at least one selected from the group consisting of Al, Si, V, Nb, Mo, Ta, Y, La, Sn, Zr, B, W, Mg, Ce, Hf, Ta, Ti, Sr, Ba, F, P, S, and La; 0.9≦a≦1.1, 0≦b≦0.2, 0≦c≦0.2, 0≦d≦0.1, 0<b+c+d≦0.
4.
4. The method for producing a positive electrode active material according to claim 1, wherein the primary heat treatment is performed at 660 to 790°C.
5. The method for producing a positive electrode active material according to claim 1, wherein the secondary heat treatment is performed at 660 to 780°C.
6. 2. The method for producing a positive electrode active material according to claim 1, wherein the step (S4) is carried out for 3 to 60 minutes using a water washing solution at 1 to 90° C.
7. The cobalt ion-containing source is Co(OH) 2 , Co 2 O 3 , CoCO 3 , Co 5 (CO 3 ) 2 (OH) 6 , Co 3 (P.O. 4 ) 2 , CoF 3 , CoOOH, Co(OCOCH 3 ) 2 ・4H 2 O, Co(NO 3 ) 6H 2 O.C.O. 3 O 4 , Co(SO 4 ) 2 ・7H 2 O and CoC 2 O 4 The method for producing a positive electrode active material according to claim 1 , wherein the positive electrode active material is one or more selected from the group consisting of:
8. The boron coating source is H 3 B.O. 3 , B 4 C, B 2 O 3 , B.F. 3 , (C 3 H 7 O) 3 B, (C 6 H 5 O) 3 B, [CH 3 (CH 2 ) 3 O] 3 B, C 13 H 19 O 3 , C 6 H 5 B(OH) 2 and B 2 F 4 The method for producing a positive electrode active material according to claim 1 , wherein the positive electrode active material is one or more selected from the group consisting of:
9. The lithium transition metal oxide includes nickel, cobalt, and manganese, and is in the form of secondary particles formed by agglomeration of primary particles; A coating layer containing cobalt is formed on the surface of the secondary particles of the lithium transition metal oxide and on the interface between the primary particles located inside the secondary particles, and the primary particles have a cobalt content of 7.0 mol % or more based on the total metal content, The spectrum of the lithium transition metal oxide measured by TEM-EELS, which is a combination of a transmission electron microscope (TEM) and an electron energy loss spectroscopy (EELS), is a first peak located at a surface portion of the secondary particle in a region corresponding to a depth of 50 nm from the surface of the primary particle, and a second peak located at a core portion of the secondary particle in a region corresponding to a depth of 50 nm from the surface of the primary particle, The surface portion of the secondary particle is a region corresponding to a depth of 50 nm from the surface of the secondary particle, The core portion of the secondary particle is a region corresponding to a depth of more than 3 μm from the surface of the secondary particle, The positive electrode active material, wherein the first peak and the second peak are peaks in a range of 180 to 200 eV in a TEM-EELS spectrum.
10. 10. The positive electrode active material according to claim 9, wherein the intensities of the first peak and the second peak are in a range of 1:0.5 to 1:
20.
11. The positive electrode active material according to claim 9 , wherein the primary particles have a cobalt content of 10.0 mol % or more relative to the total metal content.
12. 10. The cathode active material of claim 9, wherein the lithium transition metal oxide has a concentration gradient in which cobalt gradually decreases from the surface to the center of the primary particles.
Citation Information
Patent Citations
Polycrystalline metal oxide, method for producing the same, and product containing the same
JP2014528891A
Composite positive electrode active material, positive electrode containing the same, lithium battery and manufacturing method thereof
JP2020068210A
Positive electrode active material for lithium secondary battery, method of manufacturing the same, and lithium secondary battery including the same
JP2020072092A
Positive electrode active material for secondary battery, method for producing the same, and lithium secondary battery including the same
JP2021508161A
Positive electrode active material for lithium secondary battery, method for producing the same, and lithium secondary battery including the same
JP2021508658A